2017
DOI: 10.1016/j.bj.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Entosis: The emerging face of non-cell-autonomous type IV programmed death

Abstract: The present review summarizes recent experimental evidences about the existence of the non-cell-autonomous death entosis in physiological and pathophysiological contexts, discusses some aspects of this form of cell death, including morphological, biochemical and signaling pathways that distinguish non-cell-autonomous demises from other death modalities and propose to define this new modality of death as type IV programmed cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 76 publications
1
33
0
1
Order By: Relevance
“…It’s now clear that cell death programs, such as apoptosis, necroptosis and autosis, were genetically controlled ( 12 ). As a non-autonomous cell death mechanism that involves at least two cells ( 13 ), CIC-mediated death was conceivably subjected to more complex regulation. Though due to technical limitations, a systemic screening for CIC-associated genes remains to be made.…”
Section: Discussionmentioning
confidence: 99%
“…It’s now clear that cell death programs, such as apoptosis, necroptosis and autosis, were genetically controlled ( 12 ). As a non-autonomous cell death mechanism that involves at least two cells ( 13 ), CIC-mediated death was conceivably subjected to more complex regulation. Though due to technical limitations, a systemic screening for CIC-associated genes remains to be made.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mechanisms, such as entosis, emperitosis, and homotypical cell cannibalism, have been proposed to promote CIC formation either homotypically between tumor cells or heterotypically between lymphocytes and tumor cells, which generally leads to the death of the internalized cells (5,6). The death of the engulfed cells was believed to be executed non-autonomously by the engulfing cells, so CIC structures are believed to mediate a novel type of cell death process that parallels the existing cell-autonomous death processes apoptosis, necrosis, and autosis (7). Entosis is the best studied mechanism underlying the formation of CIC structures between tumor cells, and it is driven by polarized actomyosin that is compartmentalized by p190A RhoGAP recruited to Ecadherin-mediated adherens junction (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of evidence pertaining to specific cellular fate, and the possibility for cells to escape entotic engulfment, it has now been proposed that entosis be referred to as a mode of internalisation only, and not a complete mode of cell death. In contrast, Perfettini et al have recently suggested that entotic cell death be classified as type IV non-cell autonomous cell death [78]. It becomes clear that future work is required that enables precise relation of autophagic activity with the diversity of lethal autophagic responses.…”
Section: The Molecular Distinction Between Adcd and Autosismentioning
confidence: 98%